Comprehensive Study of all-in-one Simultaneous Multiple Optical Logic Gate Devices Using Mach–Zehnder Interferometer based on the Electro-optic Effect. Issue 3 (4th May 2022) - Kumar, Manish; Kumar, Ajay; Jindal, Sumit Kumar; Raghuwanshi, Sanjeev Kumar
Abstract : A new type of cascading of Mach–Zehnder interferometer (MZI) structure is presented based on the electro-optic effect for simultaneous multiple operations of different logic families operation in this paper. Unit MZI as a switch to cascading-structure is presented, starting from the illustration of material characteristics to logic realization. It includes some exciting techniques to implement the simultaneous multiple optical logic operations through mathematical understanding along with the simulation of proposed devices using the MATLAB. After that, the realization of the proposed structure is done, on OptiBPM simulation software which provides comparative potential advantages of high-speed optical logic devices in the field of next-generation high-speed optical systems. These logic devices miniaturization may be useful for the development of a logical unit of the optical Arithmetic logic unit (ALU) of the future optical microprocessor system.